Application of Solid-State Fermentation for the Improving of Extruded Corn Dry-Milling By-Products and Their Protein Functional Properties - Daiva Zadeike; Zydrune Gaizauskaite; Mantas Svazas; Romas Gruzauskas; Valentas Gruzauskas; Jonas Damasius; Grazina Juodeikiene (Life, 2022)
In this study, the effect of solid-state fermentation (SSF) with Lactobacillus sakei MI401 and Pediococcus acidilactici PA-2 strains on functional properties of extruded (130 °C; 25 rpm) corn-milling by-products (CMB) and their albumin, globulin, and prolamin fractions was evaluated in order to produce stabilized and functionalized food/feed stock. Extrusion resulted in a considerable reduction of microbial contamination of CMB by five log cycles, increased damaged starch, water-absorption capacity, and lowered protein and fat contents by 12.4% and 37%, respectively. The application of SSF for the extruded CMB have been shown to improve the water absorption, foaming, and emulsifying capacity of albumins and globulins and also increased the digestibility and free radical scavenging activity of prolamins. The essential amino acid content (EAA) in CMB and antioxidant activity of prolamins was lowered after extrusion but significantly increased after SSF. The combination of the abovementioned treatments can be confirmed as a prospective functionalization of CMB, capable of potentially enhancing its safety and improving nutritional, biochemical, and technological properties of proteins.